Soundings at Tell al-Dhibaʿi - Mustafa, M. A.
Stratum I-II-III-IV-V — Objects — Pottery Vessels — Terracotta Figurines — Miscellaneous Objects — Burials — Summary and Dating of the Strata — List of the Objects Illustrated.